2010
DOI: 10.1111/j.1365-294x.2010.04885.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure in large, continuous mammal populations: the example of brown bears in northwestern Eurasia

Abstract: Knowledge of population structure and genetic diversity and the spatio-temporal demographic processes affecting populations is crucial for effective wildlife preservation, yet these factors are still poorly understood for organisms with large continuous ranges. Available population genetic data reveal that widespread mammals have for the most part only been carefully studied at the local population scale, which is insufficient for understanding population processes at larger scales. Here, we provide data on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 54 publications
2
52
2
Order By: Relevance
“…R. Soc. B 282: 20150092 a century ago led to at least two different populations [31,47]. Conservation-minded changes in legislation during the second part of the last century led to a controlled harvest of the species and, accompanied by immigration from Russia, resulted in increasing numbers of bears, which dispersed further north and west over time [31,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. Soc. B 282: 20150092 a century ago led to at least two different populations [31,47]. Conservation-minded changes in legislation during the second part of the last century led to a controlled harvest of the species and, accompanied by immigration from Russia, resulted in increasing numbers of bears, which dispersed further north and west over time [31,63].…”
Section: Discussionmentioning
confidence: 99%
“…Since earlier studies have shown a restricted number of genetic clusters in Finland [31][32][33]47], we used a maximum number of K ¼ 10 clusters, and assumed population admixture and correlated allele frequencies within the population. Ten independent runs for each K-value between one and 10 were performed.…”
Section: (D) Molecular Analysismentioning
confidence: 99%
“…Polar bears exhibit low levels of population differentiation at biparentally inherited and mitochondrial markers throughout their range (Paetkau et al 1999;Cronin and MacNeil 2012;Miller et al 2012;Campagna et al 2013). Brown bears, in contrast, show considerable phylogeographic structuring at mitochondrial markers (Davison et al 2011;Edwards et al 2011;Hirata et al 2013;Keis et al 2013), and population structuring can also be discerned at biparentally inherited microsatellites (Paetkau et al 1997;Tammeleht et al 2010;Kopatz et al 2012). Most mtDNA clades are confined to certain geographical regions and are not shared between continents, although one brown bear clade is widespread throughout Eurasia and extends into North America (Korsten et al 2009;Davison et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, all range-wide phylogeographic studies on brown bears have so far relied on mtDNA. Studies of autosomal markers were regionally restricted to either North America or Eurasia (Paetkau et al 1997;Tammeleht et al 2010;Kopatz et al 2012;Cahill et al 2013), and no phylogeographic study of Y chromosome markers in bears exists. However, analysis of male-specific markers is crucial to understand bear evolution in the light of their well-documented male-biased dispersal (McLellan and Hovey 2001;Zedrosser et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, our method may find utility in wide-ranging and elusive species where source-sink dynamics has gone undetected (e.g. fur-bearing species, carnivores, marine mammals [46][47][48]). Undetected source-sink dynamics has potentially negative consequences, particularly for harvested species.…”
Section: Discussionmentioning
confidence: 99%